2018
DOI: 10.1111/jdv.14849
|View full text |Cite
|
Sign up to set email alerts
|

The regular use of an emollient improves symptoms of atopic dermatitis in children: a randomized controlled study

Abstract: These results demonstrate that the regular use of emollients in children with mild-to-moderate AD reduces the severity of symptoms and, therefore, support their use as a first-line treatment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
(41 reference statements)
0
25
0
2
Order By: Relevance
“…It was not powered to compare the effectiveness of the interventions, but eczema severity improved in all groups over a 12 week period 14. An open-label study1516 randomised 335 children aged 2-6 years with mild to moderate atopic dermatitis to Dexeryl (V0034CR) cream, Atopiclair cream, or no emollient: the proportion of patients with one or more flares and the number of flares was lower in both emollient groups, with Dexeryl cream seeming to perform better than Atopiclair cream.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…It was not powered to compare the effectiveness of the interventions, but eczema severity improved in all groups over a 12 week period 14. An open-label study1516 randomised 335 children aged 2-6 years with mild to moderate atopic dermatitis to Dexeryl (V0034CR) cream, Atopiclair cream, or no emollient: the proportion of patients with one or more flares and the number of flares was lower in both emollient groups, with Dexeryl cream seeming to perform better than Atopiclair cream.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…In infants and children, the type of emollient used should be carefully chosen taking into account that urea and propylene glycol can cause irritant reactions and renal toxicity if they are absorbed systemically. regular use of emollients in children with mild to moderate aD reduces flares and corticosteroid consumption and, therefore, supports their use as a first-line treatment for these patients (13,14).…”
Section: Topical Therapies Cleansing and Bathingmentioning
confidence: 78%
“…However, our findings clearly demonstrate the beneficial effects of using the study product after only 1 week. A recent study analyzing the kinetics of the response to regular emollient use in children with mild-to-moderate atopic dermatitis also found that the effects of emollients at reducing xerosis and improving SCORAD were already visible after 1 week, and that the improvements were progressive with regular emollient use over a 12-week period [41]. Further studies are required to determine if regular use of our study product over a longer period would result in further improvements in symptoms and if the symptom relief can be sustained.…”
Section: Discussionmentioning
confidence: 96%